Impact evaluation of malaria control interventions on morbidity and all-cause child mortality in Mali, 2000–2012 - Kayentao, Kassoum (Malar J, 2018)
BACKGROUND: Major investments have been made since 2001, with intensification of malaria control interventions after 2006. Interventions included free distribution of insecticide-treated nets (ITN) to pregnant women and children under 5 years old, the introduction of artemisinin combination therapy (ACT) for malaria treatment, and indoor residual spraying of insecticides. Funders include the Government of Mali, the Global Fund to Fight AIDS, Tuberculosis and Malaria, and the US President’s Malaria Initiative. METHODS: Data from nationally representative household surveys conducted from 2000 to 2015 was used to performed the trend analysis for malaria intervention coverage, prevalence of morbidities among children under 5 years old [parasitemia and severe anaemia (< 8 g/dl)], and all-cause mortality of children under 5 (ACCM). Prevalence of contextual factors likely to contribute to ACCM were also assessed. The impact of these interventions was assessed on malaria morbidity and mortality using a plausibility argument. With the assumption that malaria contributes significantly to under-five mortality in settings with high malaria transmission, associations between malaria control interventions and all-cause under-five mortality (ACCM) were assessed taking into account other contextual factors related to child survival. RESULTS: Intervention coverage improved significantly from 2006 to 2012. Household ownership of ITN increased from 49% in 2006 to 84% in 2012. ITN use also increased over the same period, from 26% in 2006 to 69% in 2012 among children under 5 and from 28% in 2006 to 73% in 2012 among pregnant women. The coverage of intermittent preventive treatment in pregnancy (IPTp) using two or more doses of SP increased from 10% in 2006 to 29% in 2012. In 2010, 23% of febrile children under 5 received ACT, as opposed to 19% in 2012. The prevalence of Plasmodium falciparum infection increased from 2010 (38.6%) to 2012 (51.6%), followed by a decrease in 2015 (35.8%). The prevalence of severe anaemia decreased from 2010 (26.3%) to 2012 (20.6%) and continued to decline in 2015 (19.9%). An impressive decline in ACCM was observed, from 225 in 1997–2001 to 192 in 2002–2006 and 95 in 2008–2012. Changes in contextual factors such as climate, socio-economic, nutrition, and coverage of maternal and child health interventions over the evaluation period did not favour reductions in ACCM, and are therefore unlikely to explain the observed results. CONCLUSIONS: Taken as a whole, the evidence supports the conclusion that malaria control interventions substantially contributed to the observed decline in ACCM in Mali from 2000 to 2012, even in the context of continued high prevalence of parasitaemia explained by contextual factors such as climate change and political instability.